Sprachspielerei oder bewusster Sprachwechsel? Code-Switching, Bricolagen und Hybridbildungen im Gangsta-Rap von Haftbefehl - Małgorzata Derecka (Linguistische Treffen in Wrocław, 2021)
The contemporary German language surprises with ever more innovative renewal tendencies of its vocabulary. The need for language development and vocabulary renewal still seems particularly great. One of the main tendencies of language development is the internationalisation of vocabulary, which can be directly attributed to globalisation and the economic and technical revolution. Thus, this approach questions the extent to which code-switching, hybrid production and bricolages shape the language of one of Germany’s best-known rappers with an immigrant background – Haftbefehl – and contribute to his lyrics based on multilingualism becoming patchwork poetry. The analysis of the lexical and stylistic level of the well-known song “Chabos know who the babo is” revealed that Haftbefehl’s language is a kind of patchwork that does not represent an entirely defined grid for language development and leaves many questions open for future linguistic research.